The mechanical and optical properties of injection-moulded PMMA, filled with glass particles of a matching refractive index - Wildner, Wolfgang; Drummer, Dietmar (Polymers and Polymer Composites, 2017)
In this paper, the optical and mechanical properties of injection-molded plates (thickness: 1 mm) made of poly(methyl methacrylate) (PMMA) and glass particles as filler with a matching refractive index are investigated. Tests show that the orientation resulting from the injection molding process greatly affects the tensile strength and elongation at break, whereas the elastic modulus merely depends on the filling degree, which is investigated up to 13 vol.%. In terms of the optical properties, the specimens' haze depends on the difference in the refractive index between a glass and polymer. However, the absolute value of haze increases with an increasing filling degree and a decreasing particle size. Surface defects resulting from the injection molding process were found to be the primary reason for this haze even with identical RI between PMMA and glass.